Consumer Search Costs and the Incentives to merge under Bertrand Competition - Jose Luis Moraga-Gonzalez; Vaiva Petrikaite (Tinbergen Institute, 2011)
This paper studies the incentives to merge in a Bertrand competitionmodel where firms sell differentiated products and consumers search the marketfor satisfactory deals. In the pre-merger market equilibrium, all firms lookalike and so the probability a firm is next in the queue consumers follow whenvisiting firms is equal across non-visited firms. However, after a merger,insiders raise their prices more than the outsiders so consumers search forgood deals first at the non-merging stores and then, if they do not find anyproduct satisfactory enough, they continue searching at the merging stores.When search cost are negligible, the results of Deneckere and Davidson (1985)hold. However, as search costs increase, the merging firms receive fewercustomers so mergers become unprofitable for sufficiently large search costs.This new merger paradox is more likely the higher the number of non-mergingfirms.
Keywords: D40; D83; L13; 330; mergers; search; insiders; outsiders; order of search; prominence